RANCANG BANGUN SISTEM INFORMASI AKADEMIK PADA SMK BINA NUSA WISATA TANGERANG MENGGUNAKAN MODEL WATERFALL - Nu’man Musyaffa (LPPM Nusa Mandiri, 2017)
Information technology brings changes to the process flow of information very quickly, practical and dynamic. The condition is a tendency to use information technology. One is the Academic Information System which is an application designed and created and applied to process all the data related to the academic information such as school information, student data, employee data, and other academic activities. With the academic information, the system has been changed notification process information. The research focuses on identifying the needs of academic information system design in accordance with its use. Research conducted by a case study on SMK Bina Nusa Wisata Tangerang. The results showed that by identifying the needs of users, academic information systems can provide customized features that each user has different access to their respective needs. By using the waterfall method can identify the features according to user needs, These features include the processing of student data, the division of classes, teaching schedule and processing report card grades.